Cognitive Style a Predicator of Managerial Effectiveness: Study of Public and Private Sector Bank Managers in India (Global Journal of Management and Business Research, 2012)
This study was conducted to investigate the relationships between cognitive style and managerial effectiveness among different managerial levels of various public and private sector bank#x2019;s of National Capital Region (Delhi) and Haryana state of India. Datawas collected by using Cognitive Style test for Field-dependence and Fieldindependence developed by Witkin (1959) and Index of Managerial Effectiveness test devised by Walter W. Hudson(1993). A sample of 300 bank managers of senior, middle and junior level positions from three public and three private sector banks of National Capital Region (Delhi) and Haryana state of Indiawas taken for the study."Both the public and private sector bank managers exhibit higher tendency of field-dependence among the senior managers in comparison to the middle level managers who have relatively greater inclination towards field-independence. Junior level managers of both the public and private sector banks are the highly inclined towards field-independence tendency in comparison to middle and senior level managers. As F-ratio was found significant so Duncan#x2019;s multiple comparison of means test was used to examine significant differences among cognitive style means of different groups. The comparisons were made at 0.05 level of significance. The results of Duncan#x2019;s multiple comparison of cognitive style means of public bank managers revealed that junior managers and middle level managers differ significantly in their means from senior managers but junior managers did not differ significantly from middle level managers. In case of private sector managers the entire three groups differ significantly in their cognitive style means. Both the public and private sector bank managers exhibit poor tendency of managerial effectiveness among the senior managers in comparison to the middle level managers who have relatively higher degree of effectiveness in management in comparison to senior managers. Junior level managers of both the publ
Keywords: Cognitive style; Managerial Effectiveness; Field-dependence and Field-independence